2020
DOI: 10.1093/gerona/glaa040
|View full text |Cite
|
Sign up to set email alerts
|

Blueberries and Cognitive Ability: A Test of Publication Bias and Questionable Research Practices

Abstract: Accepted in Journals of Gerontology Series A: Biological Sciences and Medical Sciences BLUEBERRIES, COGNITION, AND PUBLICATION BIAS 2 Hein et al (1) published a systematic review of the effects of blueberries on cognitive performance, finding that benefits may be observed for delayed memory, executive functioning, and psychomotor functioning in healthy children, healthy older adults, and/or older adults suffering from mild cognitive impairment (MCI). The purpose of the following analyses was to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…Appropriate sampling should in fact consider a small expected effect size. Indeed, study sample size and other research best practices in the wider field of nutrition and cognition have received commentary, including by Brydges and Gaeta [118] who found publication bias in the blueberry and cognition studies reviewed by Hein et al [119] However, it should be noted that the analysis by Brydges and Gaeta used p-values drawn from only the key findings from the individual studies and were not representative of all reported results in the original papers. A subsequent reanalysis by Whyte et al accounting for all the dependent variables reported in the original source papers found no evidence of publication bias.…”
Section: Flavonoids and Cognitionmentioning
confidence: 99%
“…Appropriate sampling should in fact consider a small expected effect size. Indeed, study sample size and other research best practices in the wider field of nutrition and cognition have received commentary, including by Brydges and Gaeta [118] who found publication bias in the blueberry and cognition studies reviewed by Hein et al [119] However, it should be noted that the analysis by Brydges and Gaeta used p-values drawn from only the key findings from the individual studies and were not representative of all reported results in the original papers. A subsequent reanalysis by Whyte et al accounting for all the dependent variables reported in the original source papers found no evidence of publication bias.…”
Section: Flavonoids and Cognitionmentioning
confidence: 99%
“…Those problems included publication bias and an inability to reproduce some of the calculations. 6,7 It may be important to note that both the systematic review and this trial were funded by the Wild Blueberry Association of North America.…”
Section: If One Looks Carefully At Figuresmentioning
confidence: 99%
“…The previously cited systematic review suggesting that there may be benefits to the memory from blueberries 1 also came under criticism for methodologic problems. Those problems included publication bias and an inability to reproduce some of the calculations 6,7 . It may be important to note that both the systematic review and this trial were funded by the Wild Blueberry Association of North America.…”
mentioning
confidence: 99%
“…In addition, risk of bias assessments within and across studies (#15, 19, and 22) should be included to formally assess the quality and certainty of the research in a standardized manner. Indeed, a recent analysis of the studies included in the review is suggestive of publication bias and/or other questionable research practices (7). Further, 3 of the 11 studies employ crossover designs, which are appropriately described within the text, but the authors mislabel some designs in the Tables and in the discussion: "… all but two studies (39, 45) employed a double-blind crossover, placebocontrolled design….…”
mentioning
confidence: 99%